“DEI is Unlawful”: Examining Academic Libraries’ Response as Institutional Isomorphism - Regina Gong; Silvia Vong (The Political Librarian, 2025)
Recent rollbacks of diversity, equity, and inclusion (DEI) initiatives in US academic libraries are not isolated decisions, but patterned responses to intensifying political and legal pressures. Drawing on DiMaggio and Powell’s (1983) theory of institutional isomorphism, we analyze how coercive pressures (e.g., federal and state actions), mimetic pressures (e.g., copying perceived peer responses), and normative pressures (e.g., professional expectations) have driven three interconnected shifts: the renaming or elimination of DEI positions and offices, the scaling back of DEI programming and community outreach, and the depoliticization or narrowing of DEI-related professional development. We argue that the same isomorphic mechanisms that enabled libraries to rapidly adopt visible DEI structures after 2020 also produced standardized, symbolic reforms that were weakly rooted in structural change and thus easily dismantled in the face of backlash. Writing from our positionalities as Women of Color library practitioners and scholars, we show how these intertwined pressures expose the limits of isomorphic compliance and call for equity work that is locally grounded, community-accountable, and less vulnerable to rapid cycles of expansion and retrenchment.
Keywords: institutional isomorphism; isomorphic pressures; diversity; equity; inclusion; DEI; academic libraries